2013
DOI: 10.1589/jpts.25.177
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Rehabilitation Program for Ice Hockey Players with Shoulder Injury

Abstract: Abstract.[Purpose] The purpose of this study was to evaluate the effectiveness of rehabilitation training, using elastic bands and a body blade, for ice hockey players with confirmed diagnosis of shoulder joint instability. [Methods] The subjects of this study were healthy adult ice hockey players without shoulder instability (control group, n=9) and adult ice hockey players with shoulder instability (training group, n=9). We implemented a rehabilitation training program using elastic bands and a body blade f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The article on glenohumeral dislocations in a journal [8] describes a case study where the researchers documented pain relief for a patient with a glenohumeral dislocation. The therapy method involving elastic bands and a body blade workout showed a demonstrable stabilising impact on nine ice hockey athletes suffering from shoulder weakness [29]. In order to have proper training for the Bodyblade exercise with the SAPS type of athletes, a greater training group is required made up of athletes that have a greater variety of and in greater in difficulties compared to the other types of programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article on glenohumeral dislocations in a journal [8] describes a case study where the researchers documented pain relief for a patient with a glenohumeral dislocation. The therapy method involving elastic bands and a body blade workout showed a demonstrable stabilising impact on nine ice hockey athletes suffering from shoulder weakness [29]. In order to have proper training for the Bodyblade exercise with the SAPS type of athletes, a greater training group is required made up of athletes that have a greater variety of and in greater in difficulties compared to the other types of programme.…”
Section: Resultsmentioning
confidence: 99%
“…One of the ways of helping an aching patient heal is to use a type of treatment called kinesio taping, in which taping is applied to someone's body. After this is done, the injured area feels better [29]. When these studies were done using the Bodyblade exercise, the results showed that it could be an alternative solution to traditional exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The isokinetic test for internal/external shoulder rotation is a very objective and accurate way of measuring shoulder muscle strength. Many researchers have used isokinetic muscle examination to measure shoulder stability 17 , 18 , 19 ) . Accordingly, this study compared shoulder internal/external peak torque data at angular speeds of 60°/sec and 180°/sec with CKCUES data, and found high correlations for all the results.…”
Section: Discussionmentioning
confidence: 99%